SOCIAL DEIXIS ANALYSIS IN THE FINAL INTERVIEW WITH THE OBAMAS - Erfina Nuryusticia; Dian Nurrachman (Universitas Islam Negeri Sunan Gunung Djati, 2021)
The final interview with Obama, as one of influential persons in the world, attracted many media to broadcast. His interview showed real-life interaction of a representative figure so that the way he used language is also representative. Specifically, this study aims at finding out the kinds of social deixis and to describe the function of social deixis in The Final Interview with the Obamas. The data are analyzed in a qualitative descriptive method to point out the phenomena of social deixis in the news as a part of daily life and since the collection of the data are mostly analyzed by using description and explanation form which focus on the characteristics, types, and the reason why the usage of social deixis is the main issues to be investigated. Based on the analysis of The Final Interview with The Obamas from the PeopleTV YouTube channel, it can be concluded that all types of social deixis according to Levinson’s theory are found in the object of research. There are relational which manifested by the speaker and referent, the speaker and addressee, the speaker and bystander, and the speaker and setting. There is also absolute social deixis which is manifested by the authorized speaker, and the authorized recipient absolute social deixis. In addition, the three functions of social deixis are also found in the utterances in The Final Interview with The Obamas. Those are the social status differentiation function, politeness function, and social identity function. Keywords: Social Deixis; Interview; Pragmatics